2008
DOI: 10.1088/0957-4484/19/22/225604
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of novel porous anodic alumina membranes by two-step hard anodization

Abstract: Porous anodic alumina (PAA) membranes with highly ordered hexagonal cells and a novel pore structure have been fabricated by two-step hard anodization in a H(2)SO(4)-Al(2)(SO(4))(3)-H(2)O system at 40 and 50 V, giving average cell diameters of 77 and 96 nm, respectively. There are several tiny pores embedded in each big shallow pore on the top of the membranes, and there is only one pore in one cell at their bottom. The cells on both sides of the membranes present almost the same periodic arrangement. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 19 publications
3
74
0
Order By: Relevance
“…To widen the self-ordering windows of porous AAO, Chu et al reported HA processes in sulfuric acid electrolyte, and porous AAO with a "smooth separated tubes" morphology have been realized. Similar results have also been reported by [35,53,55]. In addition, Li et al reported the fabrication of porous AAO in an ethanol modified oxalic acid electrolyte, and the as prepared porous AAO is also made up of separated tubes, and apparent thickness variations can be observed on the tube walls [56,57].…”
Section: Microstructural Morphologies Of Porous Aaosupporting
confidence: 79%
See 1 more Smart Citation
“…To widen the self-ordering windows of porous AAO, Chu et al reported HA processes in sulfuric acid electrolyte, and porous AAO with a "smooth separated tubes" morphology have been realized. Similar results have also been reported by [35,53,55]. In addition, Li et al reported the fabrication of porous AAO in an ethanol modified oxalic acid electrolyte, and the as prepared porous AAO is also made up of separated tubes, and apparent thickness variations can be observed on the tube walls [56,57].…”
Section: Microstructural Morphologies Of Porous Aaosupporting
confidence: 79%
“…Fig. 1.14 The D int -U curve of HA processes in commonly used electrolyte system: the data marked by green squares were reported in [53], by red circles were reported in [25], by blue triangles were reported in [54] Their findings further confirm that the linear relationship between U and D int is only a special case [54,55]. To explain the related intrinsic mechanisms, Lee et al assumed that a larger J will result in a higher mechanical stress at the metal/oxide interface, which may be responsible for the reduced ζ HA .…”
Section: Hard Anodizationmentioning
confidence: 57%
“…The resulting mean pore diameter of membranes was of the order of 50 nm, with a separation between pores of 100 nm for the oxalic acid at 50 V, called normal anodization (NA) process and 100 nm of pore sizes with 250 nm of interpore distance by using oxalic acid at 100 V, denominated hard anodization (HA) process. 16 The interpore distance of each sample is directly related to the bumps mean diameter in the oxide barrier layer, which implies that our sample set is composed by hexagonal domes arrangement with 100 and 250 nm of diameter.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…52 Xu and co-workers reported that there existed on the optimal amount of ethanol addition into the acidic electrolyte, which was typically used as a coolant for HA, [46][47][48][49] for increasing AAO growth rate under MA condition. 53 For separating an AAO from the Al substrate, toxic chemicals containing heavy metal ions, such as mercury chloride 5,6,19,21,37,[54][55][56][57] or copper chloride (CuCl 2 ) 42,48,58,59 are commonly used for dissolving the remaining part of the Al substrate, which is another timeconsuming part in the conventional AAO fabricating methods. The chemical etching and AAO separation time could be reduced a little by adding hydrochloric acid into CuCl 2 aqueous solution, 10,30,[43][44][45] however, these chemical etching-based AAO separation methods show critical disadvantages in terms of environmentally hazardous residues and dissipating valuable resources.…”
Section: Introductionmentioning
confidence: 99%